A review on Reliability, Security and Memory Management of Numerous Operating Systems - Mohammad Marufuzzaman; Shafin Al Karim; Md Saifur Rahman; Noor Mohammad Zahid; Lariyah Mohd Sidek (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
With the improvement of technology and the growing needs of computer systems, it is needed to ensure that operating systems are able to provide the required functionalities. To provide these functionality operating systems are designed to maintain some design factors such as scalability, security, reliability, performance, memory management, energy efficiency. However, none of these factors can be achieved directly without facing any challenges. This research studied several design issues that are connected to each other in terms of providing an effective result. Therefore, this review article tried to reveal the major issues, which are independently more complex to solve at once. Finally, this research provides a guideline to overcome the challenges for future researchers by studying many research articles based on these design issues.